2021
DOI: 10.3390/foods10102263
|View full text |Cite
|
Sign up to set email alerts
|

Moroccan Strawberry Tree (Arbutus unedo L.) Fruits: Nutritional Value and Mineral Composition

Abstract: The strawberry tree (Arbutus unedo L.), grown throughout the Mediterranean, produces edible fruit; as it is easily bruised, the sweet, reddish fruit is used mostly to prepare jams, marmalades and alcoholic beverages. As the genus is paraphyletic, phytochemical analysis can assist in defining the fruit composition with the species Arbutus unedo L. (A. unedo). Here we report on the carbohydrate, total sugar, protein, fat, fiber, ash, and mineral content of wild fruit, harvested from 45 specimens from five locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…56 Many phytochemical compounds have been reported in the AUAE, including vitamins, carotenoids, flavonoids, polyphenols, and tannins, and their derivatives are the most prevalent. [57][58][59][60][61] CMAE contains high levels of numerous valuable secondary metabolites especially flavonoid, vitamin C, glycoside, anthocyanin, saponin, tannin, and phenolic compounds. [62][63][64][65] According to the phytochemical compound findings, the results concerning the A. unedo polyphenolic contents are higher than another study which found it between 9.51 and 19.73 mg GAE/g, DW).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Many phytochemical compounds have been reported in the AUAE, including vitamins, carotenoids, flavonoids, polyphenols, and tannins, and their derivatives are the most prevalent. [57][58][59][60][61] CMAE contains high levels of numerous valuable secondary metabolites especially flavonoid, vitamin C, glycoside, anthocyanin, saponin, tannin, and phenolic compounds. [62][63][64][65] According to the phytochemical compound findings, the results concerning the A. unedo polyphenolic contents are higher than another study which found it between 9.51 and 19.73 mg GAE/g, DW).…”
Section: Discussionmentioning
confidence: 99%
“…Many phytochemical compounds have been reported in the AUAE, including vitamins, carotenoids, flavonoids, polyphenols, and tannins, and their derivatives are the most prevalent. 57-61 CMAE contains high levels of numerous valuable secondary metabolites especially flavonoid, vitamin C, glycoside, anthocyanin, saponin, tannin, and phenolic compounds. 62-65…”
Section: Discussionmentioning
confidence: 99%
“…Long time used for human and well-being purposes, the strawberry tree leaves and fruits are presently the subjects of a profusion of studies on their chemical and biochemical composition and respective biological activities [ 3 , 4 , 5 , 6 , 7 ], which have already extended to roots [ 8 ] and derived products (e.g., distillates) [ 2 , 9 ]. All this research activity has led to the publication of several reviews on this wide topic [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, a detailed analysis of the scientific literature was conducted to confirm the safe usage of the chosen plant materials and their by-products. A. unedo fruits are eaten fresh and are well known for being processed mainly into alcoholic drinks, marmalades, jams, and jellies [25,26]; no toxic effects were reported [27]. M. communis berries are edible [28,29], and the most known application is the hydroalcoholic infusion of myrtle berries in order to obtain the famous Sardinian sweet liqueur [30].…”
Section: Introductionmentioning
confidence: 99%